Efektivitas E-booklet Tentang ASI Eksklusif dalam Peningkatan Pengetahuan dan Sikap Ibu Hamil Trimester III: Effectiveness of an E-booklet on Exclusive Breastfeeding in Enhancing Knowledge and Attitudes of Third-Trimester Pregnant Women - Purba, Edy Marjuang; Sandy, Yatty Destani; Damanik, Kanaya Yori; Purba, Saut; Nainggolan, Anna Waris (Universitas Airlangga, 2024)
Background: Knowledge and attitudes of third-trimester pregnant women significantly affect the success of exclusive breastfeeding. This period is critical for mothers to prepare for childbirth, including understanding infant nutrition. Enhancing knowledge and attitudes requires effective media aligned with technological advancements, such as an E-booklet. Objectives: To evaluate the impact of an E-booklet on exclusive breastfeeding in enhancing the knowledge and attitudes of third-trimester pregnant women in the Tuntungan Health Center area. Methods: This quasi-experimental study used a pre-test and post-test design with a control group. A total of 60 third-trimester pregnant women (30 in the experimental group and 30 in the control group) were chosen through purposive sampling. The intervention consisted of distributing an E-booklet over a two-week period. Changes in knowledge and attitudes were evaluated using the Wilcoxon and Mann-Whitney tests. Results: Most participants in both groups were aged 20–25 years (50.0% and 56.7%), had higher education (73.3% and 70.0%), parity ≤2 (63.3% and 66.7%), were unemployed (63.3% and 56.7%), and had high incomes (60.0% and 56.7%). The experimental group showed a mean knowledge score increase of 5.70 (SD=2.57) compared to 0.86 (SD=1.37) in the control group. Attitude scores increased by 8.87 (SD=3.37) in the experimental group compared to 1.43 (SD=3.65) in the control group. Mann-Whitney analysis indicated that the E-booklet significantly improved knowledge and attitudes (p-value=0.001). Conclusions: The E-booklet effectively enhanced the knowledge and attitudes of third-trimester pregnant women regarding exclusive breastfeeding. It is a promising educational tool to promote exclusive breastfeeding in communities.